PERAN PELATIHAN MOTIVASI KERJA DAN KUALITAS PELAYANAN TERHADAP MINAT MASYARAKAT PEMBAYAR PAJAK KENDARAAN BERMOTOR PASCA PANDEMI DI NUSA PENIDA KLUNGKUNG BALI - Sisi Octa Puspitasari Ni Putu; Merta I Ketut; Arya Pering I Made (Widyadari, 2024)
This study aims to examine the role of training, work motivation and service quality on people’s interest in paying motorized vehicle taxes in Nusa Penida Klungkung Bali after the pandemic. Using human resource theory and applied theory of human resource competence, motivation and entrepreneurship. Qualitative research methods using a questionnaire with 75 samples and four hypotheses assisted by data processing using SPSS version 24. The results of the study obtained 1. Work motivation has a positive and not insignificant effect on people’s interest in paying taxes. 2. Quality of service has no significant effect on people’s interest in paying taxes, 3 Training variables mediate work motivation and service quality on people’s interest in paying taxes, 4. Path analysis shows that there is a direct influence between the variables Work Motivation, Service Quality and Training on Community Interests Paying taxes produces a low direct effect on people’s interest in paying taxes and an indirect effect between the Effect of Work Motivation through Training on people’s interest in paying moderate or moderate taxes. The implications of the influence of Work Motivation, Quality of Service and Training on Public Interests to Pay Taxes are lower and are more influenced by other factors